Psychophysiological effects of a supervised home-based resistance band exercise program in pre-frail older patients with type 2 diabetes mellitus: a randomized controlled trial - Lin Hu; Haixia Feng; Jing Han; Qing Han; Yumin Zhang (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Frailty is a syndrome as with aging in the population of type 2 diabetes mellitus (T2DM) and exercise has become an essential non-pharmacological tool especially in the pre-frail stage. Notably, the form of supervised home-based exercise program has been strongly recommended in recent years. This study aimed to verify the potential effects of the supervised home-based elastic band exercise in pre-frail older T2DM patients in China. Methods A total of 100 participants were included and randomly divided into intervention group (IG) (n = 50) and control group (CG) (n = 50). The CG received a routine care, while the IG received an extra home-based elastic band training under online and offline supervisions sustaining 12-weeks. The glycosylated hemoglobin (HbA1c), blood lipids, body composition, physical function, scales of Diabetes specificity quality of life scale (DSQL), Pittsburgh sleep quality index (PSQI) and short form geriatric depression scale (GDS-15) of the participants were evaluated before and after intervention. Results The average age of the participants were 66.01 ± 4.76 with 55% male and average BMI 24.75 ± 3.51 kg/m2. The clinical characteristics of the two groups were comparable. After 12 weeks’ training, muscle mass of the limbs (P < 0.05), physical function indicators including grip strength, chair stands (both P < 0.05), walking time (P < 0.01), HbA1c (P < 0.05), frailty score (P < 0.05), subjective sleep quality (P < 0.05), total DSQL scores (P < 0.01) and the depressive status (P < 0.01) improved significantly in IG when compared with CG. Conclusion Supervised home-based elastic band exercise could improve limb muscle mass, physical fitness, glucose and lipid control and quality of life in pre-frail older T2DM patients. Trial registration number ChiCTR2300070726; Registration date: 21/04/2023.